Caught in the Crossfire: Examining the Mediating Effects of Negative Emotion on the Relationship Between Interparental Conflict and Behavior Problems - Riaz, Saba; Babar, Shehroz; Khan, Usama (Pakistan Journal of Humanities and Social Sciences, 2024)
Behavioral problems are more prevalent in children belonging to conflictual families. Therefore, the aims of current study encompass to explore the potential links between interparental conflict and behavior problems and whether this relationship is mediated by negative emotions. A cross-sectional research design was implemented to recruit 200 participants within age range of 15-20 years, having a mean age of 18.75 years (SD = 1.15) conveniently. The main standardized assessment tools administered in this study were Child Perception of Interparental Conflict Scale (CPICS), Positive and Negative Affect Schedule- Short Form (PANAS-SF) and Behavior Problem Scale (BPS). Results revealed that interparental conflict was significantly linked with negative emotions and behavior problems respectively. Furthermore, interparental conflict and negative emotions were significantly predicting behavior problems in the recruited adolescents. Mediation analysis indicated that negative emotions were significantly mediating the association between interparental conflict and behavior problems. Results of the current study are discussed in the light of relevant literature.